Legality Letter of Statement of Khilaf in Indonesia Criminal Justice System - Rugun Romaida Hutabarat (Universitas Lampung, 2018)
In criminal law, a person charged with a criminal offense may be punished if it meets two matters, namely his act is unlawful, and the perpetrator of a crime may be liable for the indicated action (the offender's error) or the act may be dismissed to the perpetrator, and there is no excuse. The reasons may result in the death or the removal of the implied penalty. But it becomes a matter of how if the Letter of Statement Khilaf is the answer to solve the legal problems. The person who refuses or does not do what has been stated in the letters is often called